Phytochemical profiles and bioactivities from hystrix brachyura bezoar extracts using maceration and ultrasonication - Faizah Abdullah Asuhaimi (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
Porcupine bezoar (PB) has been traditionally claimed to be able to cure various type of diseases. However, the effect of extraction method on its biological activity and phytochemical profile has never been studied. Hence, three different types of PB namely, blood date (PB1), powdery date (PB2) and grassy date (PB3) were initially procured then extracted using sonication method (30 minutes for 3x) and evaluated for their antioxidant potentials through determination of total phenolic content (TPC) and total flavonoid content (TFC). Moreover, 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was also carried out to confirm free-radical- scavenging effect of all PBs extracts. Based on the results obtained, PB3 was chosen for the next phase of analysis and subjected to both maceration (72h at room temperature in magnetic stirrer) and sonication extraction method (30 minutes for 3x). In this regard, the antioxidant activities of both PB3 aqueous extracts obtained through maceration (PB3M) and sonication (PB3S) extraction methods were further evaluated using dot-blot (in DPPH, ABTS and β-carotene solution), TPC, TFC and DPPH assays. The phytochemical analysis was performed by gas chromatography–mass spectrometry (GC-MS) and anticancer screening was performed on three different types of cancer cell lines viz. malignant melanoma cell line (A375), cervical carcinoma cell line (HeLa) and breast adenocarcinoma cell line (MCF7). Normal HDF cells were used as control. The TPC value of the PBs showed increasing order from PB3 (5.56 ± 0.29 μg GAE/5 mg dry extract) < PB2 (7.70 ± 0.14 μg GAE/5 mg dry extract) < PB1 (8.00 ± 1.19 μg GAE/5 mg dry extract). All three PBs were devoid of flavonoids with negative values (PB1, -26.29 μg QE/5 mg dry extract, PB2, -23.30 μg QE/5 mg dry extract, PB3, -4.10 μg QE/5 mg dry extract). Among all the extracts, PB3 exhibited good radical-scavenging activity with >50% inhibition on DPPH radical. The dot-blot assay for PB3M and PB3S showed similar result in all three types of solutions. PB3S showed higher TPC value (5.56 ± 0.29 μg GAE/5 mg dry extract) and lower IC50 of DPPH assay (75.81 ± 7.33 µg/mL) compared to PB3M (4.55 ± 0.04 μg GAE/5 mg dry extract and 458.82 ± 15.80 µg/mL respectively). Both extracts were devoid of flavonoids. GC-MS analysis revealed myristic acid, ursodeoxycholic acid, pentadecyl acrylate, 2-palmitoylglycerol and stearic acid as the main bioactive compounds in PB3M while ursodeoxycholic acid, 17α-Hydroxypregnenolone, pentadecyl acrylate, stearic acid and 1-Dodecanol were detected as the main bioactive compounds in PB3S. The anti-proliferation assay showed similar inhibition results on A375 and MCF7 cells for both the extracts (PB3M and PB3S) while on HeLa cell, PB3M (1.27 ± 0.07 µg/mL) was found to be the more potent than PB3S (1.93 ± 0.07 µg/mL) with lower IC50 value. As conclusion, PB3 demonstrated better antioxidant activities compared to PB1 and PB2. PB3S, the aqueous extract obtained through sonication method, exhibited good antioxidant activities, higher abundancy of phytochemicals and similar anti proliferative activity on cancer cell lines compared to that of PB3M, the aqueous extract obtained through the maceration method. Hence, PB extract obtained through sonication technique is expected to manifest better biological effect and could prove more beneficial. However, more in-depth studies are still warranted to further confirm PB extract's beneficial effects to treat different disorders.